Relationship between monsoon and infaunal Polychaeta in the mangroves of Tok Bali, Pasir Putih, Kelantan, Peninsular Malaysia - Kassim, Zaleha; Md. Bidin, Zaleha; Ismail, Norshida (Malaysian Nature Society, 2020)
Mangrove forest is known for the important natural resources and tree species that might have medicinal and authentic values. The forest floor is expected to support high diversity of polychaetes which is important in the decomposition process. This study aimed to investigate the effect of environmental condition on the infaunal polychaetes inhabiting the forest floor in relation to the change of monsoon for dry (July), pre-monsoon (September) and monsoon (December) in 2005. Polychaeta samples were obtained by sieving the top 6cm sediment of the forest floor using a 500 microns sieve. The species, Neries unifasciata, Namalycastis indica, Capitella capita, Chone collaries, Syllis trifalcata, Ampherete agulhanis, Parasclerocheilus capensis, Potamilla reniformis and Leonates decipiens were identified which generally errant species. The temperature, dissolved oxygen, pH and salinity were significantly correlated with the monsoon season but not with the polychaetes. Density of polychaetes correlates negatively with season (r = -0.657) and TOM (-0.580) at p<0.05 as shown by the Pearson-Rank Correlation Test. The infaunal polychaetes, received less influence from the surface water thus maintained their abundance despite the changes in monsoon season. More inclusive data can be obtained through a long-term study in the area.